The effect of corncob biochar application and dose reduction of N, P, K fertilizer on growth and yield of soybean (Glycine max L.) in regosol soil, Bantul, Yogyakarta - Risda Yunita Nurjanah; Didik Indradewa; Siti Nurul Rofiqo Irwan (Jurnal Ilmu Pertanian, 2022)
During the period of growth and development, soybeans need loose soil that is rich in organic matter. Biochar is a soil amendment with high porosity and large surface area, resulting in nutrients and water to be well absorbed and retained. Intensive agricultural cultivation requires a supply of nutrients by the application of inorganic fertilizers such as N, P, and K. Organic matter needs to be applied to maintain soil fertility and balancing the dose of inorganic fertilizers. The study aimed to determine the effect of corncob biochar application and the dose reduction of N, P, K fertilizer on the growth and yield of soybean. The research was conducted from November 2020 to March 2021, located at Tridharma Farm, Yogyakarta. Randomized complete block design was used with the application of 10 t/ha of biochar and without biochar as the first factor. The second factor was the use of N, P, K fertilizers in 100%, 75%, 50%, and 0% of recommended doses. The application of biochar 10 t/ha on soybeans was able to increase physiological components which include stomatal opening, stomatal density, and N, P, K uptake; growth components which include root length density, root area density, leaf area, leaf area index, net assimilation rate, crop growth rate, plant dry weight, harvest index, and yield components which include number of nodes and pods per plant, 100 seed weight, grain weight per plant and grain yield. Dose reduction of fertilizers did not lead to decreasing the physiological activity, growth, and yield of soybeans.